2019
DOI: 10.1111/geb.12994
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi in European grasslands under nutrient pollution

Abstract: Aim Our aim was to quantify the extent to which nutrient pollution explains arbuscular mycorrhizal fungal community richness and composition. Location Europe. Time period 2014–2016. Major taxa studied Arbuscular mycorrhizal fungi. Methods We sampled soils of calcareous and acidic grasslands and roots of 34 host plant species across a large geographical gradient of atmospheric nitrogen deposition and soil phosphorus availability. Furthermore, we performed an independent pairwise comparison between fertilized an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 59 publications
3
38
0
Order By: Relevance
“…This result was similar to that of a regional-scale research in European grasslands (Ceulemans et al, 2019), which found that soil available P had a significant negative relationship with AM fungal richness.…”
Section: N Addition Effects On Am Fungal Richness and Diversitysupporting
confidence: 90%
“…This result was similar to that of a regional-scale research in European grasslands (Ceulemans et al, 2019), which found that soil available P had a significant negative relationship with AM fungal richness.…”
Section: N Addition Effects On Am Fungal Richness and Diversitysupporting
confidence: 90%
“…In this context, our results do not point towards a critical load of nitrogen deposition below which there are no harmful environmental consequences, contrary to current environmental policy (Payne et al ., 2017). In line with a recent study on arbuscular mycorrhizal fungi in European grasslands, areas of zero‐pollution or as low as possible are the only effective environmental conservation strategy for ericoid mycorrhizal fungi (Ceulemans et al ., 2019). This is particularly the case in bogs, where atmospheric nitrogen deposition showed a clear negative relationship with mycorrhizal fungal richness.…”
Section: Discussionmentioning
confidence: 99%
“…van der Linde et al ., 2018; Lilleskov et al ., 2019) and arbuscular mycorrhizal fungi from grassland and agricultural ecosystems are negatively affected by nutrient enrichment (e.g. Leff et al ., 2015; Jiang et al ., 2018; Ceulemans et al ., 2019). Although it can be expected that ericoid mycorrhizal fungi will respond similarly to nutrient pollution, empirical evidence is still lacking, particularly on a large geographical scale.…”
Section: Introductionmentioning
confidence: 99%
“…Our results emphasized that both abundant bacterial and fungal sub-communities had higher niche breadths, which re ected their adaptations to broader ranges of environmental gradients. Environmental threshold analysis based on TITAN has been reported in some biodiversity-related studies [17,30,55]. For instance, ectomycorrhizal fungal diversity in North American…”
Section: Discussionmentioning
confidence: 99%
“…Rare and abundant microbial taxa show diverse responses to environmental change [22,25]. Environmental thresholds of arbuscular mycorrhizal fungi in European grassland are estimated using the accumulated values of change points of all the species in a given microbial community [30]. Procurable environmental thresholds rarely integrate the abundance, occurrence, and directionality of microbial responses at the species level, and little research is based on standardized phylogenetic and molecular evolutionary analysis of natural sites on a large spatial scale [17,31].…”
Section: Introductionmentioning
confidence: 99%